The school immersed in media - chances and threats - Janusz Miąso (Maria Curie-Skłodowska University, Lublin, Poland, 2017)
Stanisław Dylak claims significantly: "The school itself has never been under such pressure from the environment that it is experiencing nowadays", since nowadays media environment has been trying to introduce a well-planned education as well as to inspire and trigger immense socialization in terms of span and effectiveness. Never before have pupils had such "space" as they do today, the media space, digital space where they can spend their time, make friends, have fun with friends from the furthest places in the world. The school used to provide just an ersatz of that (Dylak 2013, p. 12). Therefore, the question about the future of the school is the one that is exploding today with great impetus. In my opinion, the school is and will be essential mainly because of a real socializing process that is performed via real interactions among pupils and with their teachers. At the same time, I am convinced that the school will be slightly different, it will be an interactive school in which we will observe professionalizing and intensification of interpersonal communication as well as interactive didactics which enables a very dynamic education process in good atmosphere, using the pupil's potential and with a wise use of media. A path leading to such a school is not easy as there are as many opportunities as difficulties and threats on the road but "it is the living we must follow, and leave the former life beneath..." (Adam Asnyk, transl. Jarosław Zawadzki).